2004
DOI: 10.1002/jcb.20059
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐apoptotic effects of curcumin on photosensitized human epidermal carcinoma A431 cells

Abstract: Photodynamic treatment (PDT) can elicit a diverse range of cellular responses, including apoptotic cell death. Previously, we showed that PDT stimulates caspase-3 activation and subsequent cleavage and activation of p21-activated kinase 2 (PAK2) in human epidermal carcinoma A431 cells. Curcumin, the yellow pigment of Curcuma longa, is known to have anti-oxidant and anti-inflammatory properties. In the present study, using Rose Bengal (RB) as the photosensitizer, we investigated the effect of curcumin on PDT-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 66 publications
2
62
0
Order By: Relevance
“…8 Systematic preclinical safety studies orchestrated by the US National Cancer Institute (NCI) did not discover any adverse effects in rats, dogs, or monkeys at doses of up to 3.5 g/kg administered up to 3 months in duration. 24 One early report suggested a potentially ulcerogenic effect of dietary curcumin in the stomach of the albino rat, 67 but this finding has not been replicated in subsequent rodent studies. In more recent preclinical investigations of dietary curcumin, toxicity has not been observed at 2% of the diet in rats 16 (approximately 1.2 g/kg) or at 0.2% of the diet in mice 31 (approximately 300 mg/kg).…”
Section: Safetymentioning
confidence: 99%
“…8 Systematic preclinical safety studies orchestrated by the US National Cancer Institute (NCI) did not discover any adverse effects in rats, dogs, or monkeys at doses of up to 3.5 g/kg administered up to 3 months in duration. 24 One early report suggested a potentially ulcerogenic effect of dietary curcumin in the stomach of the albino rat, 67 but this finding has not been replicated in subsequent rodent studies. In more recent preclinical investigations of dietary curcumin, toxicity has not been observed at 2% of the diet in rats 16 (approximately 1.2 g/kg) or at 0.2% of the diet in mice 31 (approximately 300 mg/kg).…”
Section: Safetymentioning
confidence: 99%
“…have not yet been clearly defined, studies have shown that caspase activation, MMP (mitochondrial membrane potential) changes and JNK (c-Jun N-terminal kinase) activation are critical for the mitochondria-dependent apoptotic pathway [9,14]. In addition, previous studies have shown that some apoptotic stimuli trigger heat-shock responses, such as activation of the HSPs (heat-shock proteins), which are molecular chaperones that rescue damaged proteins by facilitating their refolding [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is shown to affect the phosphorylation of MAPK1/3 and also reported to regulate the cleavage and activation of p21 (RAC1)-activated kinase 2 (PAK2). 10,[24][25][26] In addition, curcumin has also been reported to affect the autophosphorylation of epidermal growth factor receptor (EGFR) where it has also been shown to decrease phosphorylation of EGFR. 27,28 Our group has studied dysregulation in tyrosine kinases in the same cell line, Cal 27, in response to curcumin.…”
Section: Discussionmentioning
confidence: 99%